The Participation of Koptan and KUD Members Paddy Farmer in Lampung Province - Dyah Aring H.I; Masyhuri Masyhuri; Jangkung H Mulyo (Jurnal Ilmiah ESAI, 2011)
This research aims to: (1) analyze the level of member participation in the RAT, the payment of mandatory savings, and the utilization of services provided by Koptan and KUD, (2) analyze factors that influence the level of member participation.  The research is conducted with descriptive method.  Research locations specified in the three districts with the highest number of Koptan and KUD as well as dominant rice production centers in Lampung Province. They are Central Lampung, East Lampung, and South Lampung.  From each district is taken two Koptan and two KUD purposively. The sample size of farmer is 50 members of Koptan and 47 members of KUD. Member participation levels are analyzed descriptively and the factors which influence them are analyzed by multiple linear regression model. The member participation level in the RAT is high. Household income affects the Koptan member participation in the RAT negatively, while the cooperative economic benefit has a positive effect. The experiences as cooperative member and the number of dependents negatively affect KUD member participation in the RAT, while the cooperative economic benefit, non-formal education, and member satisfaction in the RAT have a positive effect. The member participation level in paying mandatory savings is moderate.  Age negatively affects Koptan member participation in paying mandatory savings, while the experiences as cooperative member and cooperative economic benefit have a positive effect.  Age positively affects KUD member participation in paying mandatory savings, while the distance from home to KUD has a negative effect. The member participation level in service utilization is low.  Number of dependents and SHU positively affect Koptan member participation in utilizing business units, while the number of cooperation has a negative effect.  The distance from home to KUD, SHU, and the suitability of the business unit positively affect KUD member participation in utilizing business units, while the number of business units has a negative influence. Keywords : member participation, koptan, KUD